1999
DOI: 10.1590/s0034-71081999000400005
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic adaptations to man-induced habitat changes by some South American Caprimulgidae

Abstract: We describe the opportunistic adaptation to man-induced changes in the habitats of six neotropical Caprimulgidae. Habitats created by those changes, and similar to their original and usual ones, are readily occupied by these nightjars. The occasional invasion of urban environments ("urbanization") is the most recent and most remarkable behavioural adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Our records indicate that it regularly breeds at the study site. Some of the areas chosen for nesting by the species are subject to intense anthropic activity, indicating an adaptability to these areas (Ingels et al 1999). A recent study found that the species also breeds in another forest fragment 30 km from Rio Branco (Lima et al 2019), indicating reasonable adaptation to the fragmented landscape of eastern Acre.…”
Section: Discussionmentioning
confidence: 97%
“…Our records indicate that it regularly breeds at the study site. Some of the areas chosen for nesting by the species are subject to intense anthropic activity, indicating an adaptability to these areas (Ingels et al 1999). A recent study found that the species also breeds in another forest fragment 30 km from Rio Branco (Lima et al 2019), indicating reasonable adaptation to the fragmented landscape of eastern Acre.…”
Section: Discussionmentioning
confidence: 97%
“…described for this species since it is in the middle of a pasture of tall tropical grasses with little to no cover by shrubs or trees [16]. Earlier observations noted that N. nigrescens occupy and reproduce in man-made habitats such as roadsides, gravel pits and laterite soils, but no mention of breeding in pastures has been made, although hunting and foraging in agricultural fields is a regular habit of this species [17].…”
Section: Observations and Discussionmentioning
confidence: 99%
“…This specimen was prepared as a study skin and has been deposited in MCNA (under the registration number MCNA 1796). Since it is known that H. longirostris has the ability to colonize large and mediumsized cities, such as Rio de Janeiro, Porto Alegre and Santo Amaro (Sick, 1959(Sick, , 1963(Sick, , 1997Ingels et al, 1999), it is very possible that this species is colonizing urban areas of Belo Horizonte. In this city, it has also been recorded in recent years in regions where it had not been detected until the last 20 years, such as the districts of Anchieta, Funcionários, Gutierrez, Luxemburgo, Mangabeiras, Santa Lúcia, Santo Antônio and Serra (L.G.M., M.F.V., C.E.R.T.B.…”
Section: Recent Colonizationmentioning
confidence: 99%